2019
DOI: 10.1142/s2661318219500051
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Learning with Large Dataset of Microscope Images to Develop an Automated Embryo Grading System

Abstract: The assessment of embryo viability for in vitro fertilization (IVF) is mainly based on subjective visual analysis, with the limitation of intra- and inter-observer variation and a time-consuming task. In this study, we used deep learning with large dataset of microscopic embryo images to develop an automated grading system for embryo assessment. This study included a total of 171,239 images from 16,201 embryos of 4,146 IVF cycles at Stork Fertility Center (https://www.e-stork.com.tw) from March 6, 2014 to Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…However, it is also misleading if the evaluated dataset is unbalanced (e.g., more negative than positive pregnancies). For instance, Chen et al [33] used a highly unbalanced Fig. 2 Confusion matrix and definitions of common binary classification metrics dataset for inner cell mass grading and reported an accuracy of 91%, which seems high compared to a random-guessing accuracy of 33%.…”
Section: Binary Classification Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also misleading if the evaluated dataset is unbalanced (e.g., more negative than positive pregnancies). For instance, Chen et al [33] used a highly unbalanced Fig. 2 Confusion matrix and definitions of common binary classification metrics dataset for inner cell mass grading and reported an accuracy of 91%, which seems high compared to a random-guessing accuracy of 33%.…”
Section: Binary Classification Metricsmentioning
confidence: 99%
“…However, it is also misleading if the evaluated dataset is unbalanced (e.g., more negative than positive pregnancies). For instance, Chen et al [ 33 ] used a highly unbalanced dataset for inner cell mass grading and reported an accuracy of 91%, which seems high compared to a random-guessing accuracy of 33%. However, due to the dataset imbalance, merely predicting the class that occurred most frequently would have resulted in an accuracy of 83%.…”
Section: Evaluation Metrics: Which Performance Measure To Use?mentioning
confidence: 99%
“…The first category's work utilized AI-based systems to assign a grade to each embryo based on the morphological attributes of various components of it [11,12,13]. Approaches of the first group tried to address the central issue around morphological grading: subjectivity to the embryologist's knowledge and experience.…”
Section: Artificial Intelligent Based Human Embryo Analysismentioning
confidence: 99%
“…A. Khan applied deep learning techniques to estimate number of cells in embryo [ 7 ]. Other study applied deep learning to develop automated embryo grading system [ 8 ]. Fully convolutional neural network model was used for embryo inner mass segmentation [ 9 ].…”
Section: Related Workmentioning
confidence: 99%